Basic Literacy Module Development for Students’ Reading Skills at Letter Level - Mukminah Mukminah; Dewi Rohiani; Siti Zainab Muslimin; Ahmad Fathir Ibnullah (Academia Open, 2025)
Background (General): Reading literacy is a foundational skill that determines students’ ability to access knowledge and succeed academically, yet Indonesian students still perform below international averages. Background (Specific): In MI NWDI Selong, many upper-grade students struggle with basic reading, indicating shortcomings in early literacy instruction. Knowledge Gap: Existing teaching methods and materials are often unsuited to young learners’ needs, lacking engaging and structured approaches to support early reading at the letter and word level. Aim: This study aimed to develop, validate, and test a basic literacy teaching module tailored for lower-grade students using the Four-D (4D) development model. Results: Expert validation produced an average feasibility score of 84%, while implementation improved students’ literacy scores from a pretest average of 39.03 to a posttest average of 79.23, demonstrating significant progress. Novelty: Unlike conventional methods, this module integrates systematic letter-to-word progression with contextual illustrations and phonetic exercises, offering a structured yet engaging tool for early literacy. Implications: The findings suggest that the developed module is both feasible and effective, providing a scalable model for improving early reading literacy in primary education contexts. Highlights: Significant improvement of students’ reading ability from pretest (39.03) to posttest (79.23). Module validated by experts with an average feasibility score of 84%. Novel approach integrates phonetic practice, letter-to-word progression, and contextual illustrations. Keywords: Teaching Module, Basic Literacy, Reading Skills, Letter Level